2002
DOI: 10.1099/00221287-148-7-2045
|View full text |Cite
|
Sign up to set email alerts
|

The genes encoding virulence-associated proteins and the capsule of Streptococcus pneumoniae are upregulated and differentially expressed in vivo

Abstract: The polysaccharide capsule of Streptococcus pneumoniae and several wellcharacterized virulence proteins are known to contribute to the pathogenesis of pneumococcal disease. However, there is a paucity of data on the expression of their respective genes in vivo. In this study, the relative abundance of the mRNA transcripts of the genes encoding pneumolysin (ply), pneumococcal surface protein A (pspA), pneumococcal surface antigen A (psaA) and cholinebinding protein A (cbpA), and of the first gene of the capsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
102
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 56 publications
3
102
0
Order By: Relevance
“…Transcription of cpsA has been shown by RT-PCR to be upregulated fourfold in bacteria recovered 24 h after intraperitoneal infection compared to expression in vitro (Ogunniyi et al, 2002). In contrast, a microarray analysis found no increase in cpsA expression in bacteria from the blood of mice compared to bacteria grown in vitro (Orihuela et al, 2004), and no difference in cpsA expression was found among bacteria isolated from the nasopharynx, lungs and blood of mice infected intranasally (LeMessurier et al, 2006).…”
Section: Introductionmentioning
confidence: 80%
“…Transcription of cpsA has been shown by RT-PCR to be upregulated fourfold in bacteria recovered 24 h after intraperitoneal infection compared to expression in vitro (Ogunniyi et al, 2002). In contrast, a microarray analysis found no increase in cpsA expression in bacteria from the blood of mice compared to bacteria grown in vitro (Orihuela et al, 2004), and no difference in cpsA expression was found among bacteria isolated from the nasopharynx, lungs and blood of mice infected intranasally (LeMessurier et al, 2006).…”
Section: Introductionmentioning
confidence: 80%
“…S. pneumoniae were grown in Todd Hewitt broth with 1% yeast extract (THY), serum broth (SB), or on blood agar, as described (2). Escherichia coli strains were grown in LB broth or LB agar (11).…”
Section: Methodsmentioning
confidence: 99%
“…We have demonstrated that several well characterized virulence genes of S. pneumoniae, including ply, pspA, psaA, and cbpA are differentially expressed under different environmental conditions (2). Of these genes, cbpA (also known as pspC) was of particular interest, because it is located only 750 nt downstream of rr06͞hk06, and a number of prokaryotic TCSTSs regulate adjacent genes on the chromosome, including the blpH͞R system from the pneumococcus (26).…”
Section: Effect Of Hk06 and Rr06 Deletion On Pneumococcal Virulence Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Lungs were removed and homogenized on ice in 2 ml sterile PBS using a tissue homogenizer (Cat X120, Germany). To separate pneumococci from host cells, lung homogenates and blood samples were centrifuged at 855 g for 6 min at 4 uC, as described previously (Ogunniyi et al, 2002). Nasopharyngeal washes, and lung and blood supernatants were subsequently centrifuged at 15 500 g for 2 min at 4 uC, and the bacterial pellet was stored at 280 uC until further processing.…”
mentioning
confidence: 99%